Faktor Faktor Pembentuk Minat Masyarakat terhadap Pembiayaan Mikro Syariah PNM Mekaar Syariah di Desa Setro - Navasya Arini Zimmy; M. Luthfillah Habibi (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze in-depth the interest of the Setro Village community in choosing PNM Mekaar Syariah financing as a source of capital for micro and small enterprises (MSMEs). This phenomenon is interesting because it shows how economic, social, and spiritual factors contribute to the financial decisions of rural communities. This research was conducted using a qualitative exploratory approach, using case studies and in-depth interviews with key informants. To explain the relationship between attitudes, subjective norms, and behavioral control on community intentions to choose Islamic financing, data analysis was conducted thematically. The Theory of Planned Behavior (TPB) framework was also used. The study shows that positive community perceptions of ease of access, economic benefits, and compliance with Islamic principles are the main factors shaping community interest in PNM Mekaar Syariah. Fast, easy, and uncomplicated financing increases consumer trust and enhances perceived behavioral control. Conversely, increased business capital and family income enhance the sustainability of micro-enterprises. The institution is given moral legitimacy and spiritual conviction by the implemented Islamic values, such as the yield system and the freedom from usury. Community participation decisions are also driven by social factors such as group support, advice from group leaders, and the quality of service provided by field officers. Theoretically, this study adds local religiosity and socio-cultural aspects to enrich the application of the Theory of Planned Behavior in the context of rural Islamic finance.